Reconstruction of Adolescent Health Care Provision Within The Indonesian Health Law System - Ely Yulian; Suparji Ahmad; Megawati Barthos (CV. Green Publisher Indonesia, 2026)
Pediatric clinics often retain a child-oriented atmosphere, which frequently causes discomfort among adolescents aged 10 to 18 who are legally still considered children but are physically and psychologically approaching adulthood. Consequently, they often refuse to seek treatment at pediatric clinics, yet they cannot be served at general adult clinics until they reach the age of 18. This study aims to: (1) analyze the legal framework governing outpatient clinic services within the Indonesian healthcare system; and (2) examine the restructuring of healthcare services for adolescents approaching adulthood to ensure legal certainty and the fulfillment of health rights. This study uses normative legal research with legislative and conceptual approaches. The results indicate that the definition of childhood in healthcare services refers to Law No. 35 of 2014, which defines a child as anyone under the age of 18. However, current healthcare practices place adolescents aged 10–18 in a transitional phase that has not been adequately accommodated in terms of service comfort and appropriateness. Therefore, regulatory reform is needed through the optimization of adolescent healthcare services, including a requirement for hospitals to provide specialized outpatient clinics for adolescents, along with adjustments to medical service policies to ensure legal certainty and the fulfillment of adolescents’ health rights in Indonesia